Multi-age-grouping paradigm for young swimmers - Kojima, K.; Jamison, P. L.; Stager, J. M. (Journal of Sports Sciences, 2012)
The purpose of this study was to examine the adequacy of "multi-age" classification systems in youth sports with a specific focus on the unisex multi-age-groupings used by USA Swimming. In addition, we offer an analytical rationale for the multi-age-groupings and potential alternatives. We examined the top 100 US swim performances for three years (2005, 2006, and 2007) for girls and boys in 15 age-groups (7 to 20 years and a singular group of 21 years and older). Data for each age and sex were pooled over the three years and means were calculated for each of seven competitive swim events. Swim times differed among each age up to the 14-year age-group in girls (F 14,30885 = 183.9, P < 0.01, Cohen's d = 1.19-3.72, large effect) and 16-year age-group in boys (F 14,30885 = 308.7, P < 0.01, Cohen's d = 0.81-3.64, large effect) for all events. Age-related differences in swim times continued later in boys than girls likely due to differences between the sexes in timing of growth and maturation. Because of the differences in swim performance in contemporary multi-age-groups, stratifying swimmers by a single age is the best means to ensure competitive fairness and equality, although there is no rationale for swimmers under the age of 8 years to compete in separate unisex competitive groups.